2013
DOI: 10.5897/ajpp12.147
|View full text |Cite
|
Sign up to set email alerts
|

A report on the analysis of 365 cases of adverse reactions of Chinese patent drugs for heart cerebrovascular diseases

Abstract: This research aimed to analyze the factors of heart cerebrovascular drugs that can lead to adverse reactions (ADRs) and to promote rational clinical drug use. Reports on cases of heart cerebrovascular diseases were collected in our hospital in 2001 to 2010, and medication and the clinical manifestations of the adverse reactions were analyzed. The incidence of adverse reactions was related with age, gender, routes of administration, dosage forms and other factors. The adverse reactions of heart cerebrovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…injection of Acanthopanax spp. in patients with cerebrovascular disease caused adverse reactions, e.g., rash, papules, nausea, vomiting, and diarrhea ( 19 ). An in vitro study revealed that ADA extracts were not mutagenic and contained anti-mutagenic activities ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…injection of Acanthopanax spp. in patients with cerebrovascular disease caused adverse reactions, e.g., rash, papules, nausea, vomiting, and diarrhea ( 19 ). An in vitro study revealed that ADA extracts were not mutagenic and contained anti-mutagenic activities ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…SMI contains the following herbs: Renshen (Radix Ginseng; Ginseng), Maidong (Radix Ophiopogonis; Dwarf Lilyturf Tuber), and Wuweizi (Fructus schisandrae chinensis ; Chinese Magnoliavine Fruit). The clinical safety of SMI has been speculated, and the adverse effects were detected in 36 patients taking SMI, including 17 male and 19 female [ 2 ]. The main adverse effect for patients taking SMI is anaphylactic reaction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinical safety of SMI has been speculated, and the adverse effects were detected in 36 patients taking SMI, including 17 male and 19 female [ 2 ]. The main adverse effect for patients taking SMI is anaphylactic reaction [ 2 ]. Additionally, clinical drug-drug interaction between SMI and warfarin was also reported [ 3 ].…”
Section: Introductionmentioning
confidence: 99%